Assessing the effectiveness of local community leaders in managing forest resources in the Mole National Park - Zakaria, Ashraf (Journal of Sustainable Tourism and Entrepreneurship, 2021)
Purpose: Protected areas remain an indispensable haven for wildlife resources, and fringe communities must participate in protected area management. Conflicts do arise amongst stakeholders and to resolve these conflicts and to get the best result out of protected areas, the co-management approach is apt, and community leaders play a major role in this direction. However, the focus of this paper is to explore how effective community leaders are in the co-management process. Research methodology: Mixed method approach was used in this study. For data collection, Questionnaire administration, Focus Group Discussions, and Key Informant Interviews were used in gathering the data. Data analysis was performed using SPSS where results were presented as descriptive statistics supported by content analysis. Findings: The study revealed that the fringe communities endorse their leaders as the most effective in protected Area management. The study also showed that both the surrounding communities and the Mole national park benefit positively from collaborative management. Limitations: Some of the community people who were sampled for the question administration were skeptical and reluctant in giving an audience to the researcher with the fear of being cited with contempt of interfering with the work of wildlife staff, but this was later resolved. In addition, the geographical scope of the study was limited to only three communities due to funding challenges. Contribution: The study could engender the development of benefit-sharing schemes in protected areas and could also lead to the discovery of eco-tourism potentials of some of the fringe communities.